Discursos imperiales: Clements R. Markham, sus viajes y obras en torno al Perú - Fernández, Christian (2016)
This article studies the most important production of the geographer, his-torian, and English traveler Clements R. Markham from an interdisciplinaryand postcolonial perspective. It takes into consideration his two books describing his two trips to Perú in the middle of the nineteenth century, his translations of the Spanish chronicles of the colonial period related to Peru,as well as his original studies on Inca culture. All this in the context of the British empire during Victoria’s reign.